Research on Older Persons’ Access and Use of Technology in the Arab Region: Critical Overview and Future Directions - Hajer Chalghoumi (19342453) (2022)
This paper presents the findings of a scoping review that maps exploratory evidence and gaps in research on information and communication technology (ICT) access and use among older persons in the Arab region. This review is part of a larger project that studies ICT access and use and related challenges faced by older adults in Qatar. A search was conducted in eleven scientific databases and search engines covering empirical studies published in English and Arabic between January 2016 and June 2021. Eleven studies were retrieved in the final corpus. A thematic analysis alongside the PRISMA for scoping reviews (PRISMA-ScR) was used to retrieve the findings. Our analysis identifies smartphones and social media applications for communication and information sharing as the most accessed and used technologies by older persons in the region. Moreover, our review highlighted the importance of the sociocultural factors in shaping ICT access and use by older persons in the region. The functional limitations of older persons in interaction with certain technology factors such as usability, functionality, and accessibility were also highlighted as major challenges inhibiting ICT access and use by this population segment. This scoping review provides a comprehensive overview of ICT access and use, and the factors affecting them among older persons in the Arab region. It highlights the scarcity of research on the subject in the region. It also stresses the fact that there is a need for more research on older persons and their caregivers in the context of the Arab world. More culturally appropriate need-based and adapted technologies are also recommended. Our review is a comprehensive source for researchers and technology developers interested in targeting and engaging older adults in the Arab region. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app12147258